The Socio-Economic and Environmental Impacts of Petroleum Refinery Operations in the Niger Delta Region - Piety Godwill Suku; Ejikeme Ugwoha; Ochuko Felix Orikpete; Daniel Raphael Ejike Ewim (The Journal of Engineering and Exact Sciences)
The Niger Delta region, a crucial hub for Nigeria's petroleum resources, encounters significant socio-economic and environmental challenges stemming from both government-owned and artisanal oil refineries. The environmental impacts, particularly air pollution and its subsequent effects on public health and the local economy, remain a primary concern. Through a comprehensive analysis of over 110 sources, this review evaluates the contributions of refinery operations to air pollution and environmental degradation in the Niger Delta. Our findings indicate that emissions from these refineries not only contribute to significant ecological imbalances but also pose severe health risks to local communities. Furthermore, the inefficiencies in refinery operations, characterized by below-standard product output and frequent accidents, have profound economic ramifications, especially for communities reliant on traditional livelihoods. The review identifies critical gaps in environmental regulations and policy enforcement, necessitating an array of solutions, including technological enhancements for better operational efficiency, the development of modular refineries, and thorough policy reforms. The study advocates for a holistic approach to surmount the environmental and health adversities triggered by refinery operations in the Niger Delta. It is imperative to integrate technological advancements, eco-friendly practices, community engagement in governance, and stringent environmental policy implementation. These strategies are vital for diminishing pollution levels and propelling sustainable economic progress within the region.